Associations of a Preoperative Anemia and Suboptimal Iron Stores Screening and Management Clinic in Colorectal Surgery With Hospital Cost, Reimbursement, and Length of Stay: A Net Cost Analysis. (23rd October 2020) - Trentino, Kevin M.; Mace, Hamish; Symons, Kylie; Sanfilippo, Frank M.; Leahy, Michael F.; Farmer, Shannon L.; Watts, Rory D.; Hamdorf, Jeffrey M.; Murray, Kevin
Abstract : BACKGROUND: In 2016, a preoperative clinic was implemented to screen, evaluate, and manage anemia and suboptimal iron stores at a major tertiary care medical center in Western Australia. Few studies compare the costs and reimbursements associated with preoperative anemia and suboptimal iron stores management. The objective of our study was to conduct a net cost analysis associated with the implementation of this clinic. METHODS: We designed a retrospective cohort study involving elective colorectal surgical admissions over a 3-year period. The baseline year selected was the 2015–2016 financial year, with outcomes in the 2016–2017 and 2017–2018 year compared to baseline. The study perspective was the Western Australian Health System. Hospital costs were extracted from the health service clinical costing system, which captures costs at the admission level. The primary outcome was net cost, defined as gross cost minus reimbursement (or funding) received. RESULTS: Our 3-year study included 544 admissions for elective colorectal surgery. After the implementation of the preoperative clinic, 73.4% (n = 257) of admissions were screened for anemia and suboptimal iron stores, and 31.4% (n = 110) received intravenous iron. In our adjusted analysis, when comparing the final year (2017–2018) with baseline (2015–2016), the units of red blood cells transfused per admission decreased 53% (142 vs 303 units per 1000 discharges; P = .006), and mean hospital length of stay decreased 15% (7.7 vs 9.1 days; P = .008). When comparing the final year with baseline, rectal resection admissions were associated with a mean decrease in the net cost of Australian dollar (A$) 7619 (95% confidence interval, 4230-11, 008; P < .001) between 2015–2016 and 2017–2018. For small and large bowel procedures, there was a mean decrease of A$6744 (95% confidence interval, 2430-11, 057; P = .002). CONCLUSIONS: The implementation of a preoperative anemia and suboptimal iron stores screening and management clinic in elective colorectal surgery was associated with reductions in red cell transfusions, length of stay, and net costs.